Oral doxycycline pharmacokinetics: Lambs in comparison with sheep. Issue 3 (30th March 2020) - Mileva, Rositsa; Subev, Sasho; Gehring, Ronette; Milanova, Aneliya
Abstract: The pharmacokinetics of doxycycline was investigated in lactating sheep and lambs after oral administration at a dose of 10 mg/kg. Concentrations in plasma and milk were assayed with HPLC‐PDA analysis. Doxycycline penetrates into the milk, and levels (0.38 ± 0.21 μg/ml) were found 0.5 hr after the treatment. The results suggest that the lambs can be exposed to doxycycline by suckling milk from their treated mothers. Population pharmacokinetic analysis showed a positive relationship between age, which reflects the stage of development of rumen function, and clearance. Possible explanations for the observed differences include the undeveloped rumen in lambs, the differences in the feed and liver function as evidenced by the blood biochemical parameters aspartate aminotransferase (AST) and alanine aminotransferase (ALT), which were significantly lower in lambs (62.67 ± 27.83 U/L and 8.50 ± 6.80 U/L) than in sheep (114.33 ± 20.77 U/L and 18.00 ± 3.16 U/L).